Germline and somatic mutations in the MTOR gene in focal cortical dysplasia and epilepsy. (December 2016) - Møller, Rikke S.; Weckhuysen, Sarah; Chipaux, Mathilde; Marsan, Elise; Taly, Valerie; Bebin, E. Martina; Hiatt, Susan M.; Prokop, Jeremy W.; Bowling, Kevin M.; Mei, Davide; Conti, Valerio; de la Grange, Pierre; et al.
Abstract : Objective: To assess the prevalence of somatic MTOR mutations in focal cortical dysplasia (FCD) and of germline MTOR mutations in a broad range of epilepsies. Methods: We collected 20 blood-brain paired samples from patients with FCD and searched for somatic variants using deep-targeted gene panel sequencing. Germline mutations in MTOR were assessed in a French research cohort of 93 probands with focal epilepsies and in a diagnostic Danish cohort of 245 patients with a broad range of epilepsies. Data sharing among collaborators allowed us to ascertain additional germline variants in MTOR . Results: We detected recurrent somatic variants (p.Ser2215Phe, p.Ser2215Tyr, and p.Leu1460Pro) in the MTOR gene in 37% of participants with FCD II and showed histologic evidence for activation of the mTORC1 signaling cascade in brain tissue. We further identified 5 novel de novo germline missense MTOR variants in 6 individuals with a variable phenotype from focal, and less frequently generalized, epilepsies without brain malformations, to macrocephaly, with or without moderate intellectual disability. In addition, an inherited variant was found in a mother–daughter pair with nonlesional autosomal dominant nocturnal frontal lobe epilepsy. Conclusions: Our data illustrate the increasingly important role of somatic mutations of the MTOR gene in FCD and germline mutations in the pathogenesis of focal epilepsy syndromes with and without brain malformation or macrocephaly.